Community Empowerment for Sustainable Cattle Farming on Post-Mining Coastal Land: A Case Study from Batu Berdaun Village, Riau Islands - Maranditya, Berliananda; Endang, Ahmat (Warta Pengabdian Andalas, 2025)
Batu Berdaun Village on Singkep Island, Lingga Regency, Riau Islands Province, faces serious challenges in developing sustainable livestock after the end of the tin mining era. The main problems include the decline in the Bali cattle population due to limited forage feed, the farmers’ limited knowledge of cattle fattening management, and the lack of utilization of livestock waste as fertilizer. Through a community engagement program, the solutions offered included training in the cultivation of odot grass (Pennisetum purpureum cv. Mott) as the main source of feed on former mining sandy lands, compost production from cow and chicken manure, and feed fermentation technology to increase nutritional value and production efficiency. The methods applied consisted of problem identification through interviews and observations, participatory training, and field demonstrations. The program results showed an increase in farmers’ understanding of forage cultivation, waste management, and sustainable cattle fattening techniques. This initiative is expected to encourage the independence of livestock groups in building a productive and competitive livestock system on post-mining coastal land.